The role and therapeutic targeting of the CCL2/CCR2 signaling axis in inflammatory and fibrotic diseases - Guo, Shan; Zhang, Qi; Guo, Yingjie; Yin, Xiaoyan; Zhang, Peng; Mao, Tao; Tian, Zibin; Li, Xiaoyu (Frontiers in Immunology, 2025)
CCL2, a pivotal cytokine within the chemokine family, functions by binding to its receptor CCR2. The CCL2/CCR2 signaling pathway plays a crucial role in the development of fibrosis across multiple organ systems by modulating the recruitment and activation of immune cells, which in turn influences the progression of fibrotic diseases in the liver, intestines, pancreas, heart, lungs, kidneys, and other organs. This paper introduces the biological functions of CCL2 and CCR2, highlighting their similarities and differences concerning fibrotic disorders in various organ systems, and reviews recent progress in the diagnosis and treatment of clinical fibrotic diseases linked to the CCL2/CCR2 signaling pathway. Additionally, further in-depth research is needed to explore the clinical significance of the CCL2/CCR2 axis in fibrotic conditions affecting different organs.